Revitalizing the Role of Educators Based on Al-Ghazali's Thoughts Amidst the Global Moral Crisis - Mashlahatud Diyanah; Putri Sitoresmi Masruroh; Moh Faizin (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2025)
This study looks at what it means to be an educator, as seen through the ideas of Imam Al-Ghazali, and places his thoughts in today's educational world. Al-Ghazali believed that educators are not just people who teach facts, but also spiritual leaders who help students grow morally and get closer to Allah. The research uses a review of Al-Ghazali's writings and modern Islamic education materials to find out what makes an ideal educator in his view. The results show that Al-Ghazali focused on qualities like good character, proper behavior, honest intentions, and patience as the key parts of being a professional educator. These ideas are still very important today, especially in dealing with moral issues, a loss of good values, and the gap between knowledge and spiritual beliefs. The study ends by saying that it is very important to bring back the role of educators as both teachers and moral guides in Islamic education to raise a generation that is both smart and good hearted.